SOCIAL EMOTIONAL LEARNING ON STUDENTS’ LEARNING MOTIVATION TO YOUNG LEARNERS - Sri Sulis Kurniawati (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2025)
This study investigates the impact of Social Emotional Learning (SEL) on the learning motivation of young learners. SEL, a framework that integrates social and emotional development into the learning process, plays a crucial role in shaping students' attitudes and behaviors toward education. By utilizing a Systematic Literature Review (SLR) method, this research synthesizes findings from various academic sources to understand how SEL programs enhance motivation among young learners. The study identifies key strategies within SEL, such as fostering self-awareness, empathy, and effective communication, that contribute to creating a positive and engaging learning environment. Findings from the review suggest that SEL implementation not only improves students’ motivation but also supports their overall academic and emotional development. This research provides valuable insights for educators and policymakers seeking to incorporate SEL into early education systems, aiming to foster more motivated and emotionally resilient learners.